The Advisability of Using Dual Gauge for Expansion of the International Traffic - Kurhan, Mykola; Kurhan, Dmytro; Husak, Marina; Hmelevska, Nelya (Printing House “Technologija”, Kaunas, Lithuania, 2020)
ENG: The possibilities of railway transport for the organization of transportation between the countries are not used to the full extent, since there are a number of technical reasons. The usage of dual gauge (1435/1520 mm) is one of the solutions. As an example of using dual gauge is the international project "Rail Baltica", Lviv railway and etc.
M. Kurhan: ORCID 0000-0002-8182-7709; D. Kurhan: ORCID 0000-0002-9448-5269, М. Husak: ORCID 0000-0001-8187-7792, N. Hmelevska: ORCID 0000-0002-2360-8671
Keywords: Rail Baltica; transport corridors; dual gauge; railway; КККГ; КПБД